The feasibility of switchgrass for biofuel production. Issue 1 (January 2012) - Mitchell, Rob; Vogel, Kenneth P; Uden, Daniel R
Switchgrass research has been conducted cooperatively by the US Department of Agriculture and the University of Nebraska since the mid-1930s, with a primary focus on bioenergy since 1990 at several institutions. Progress has been made in switchgrass breeding and genetics, molecular genetics, establishment, fertility management, production economics, production energetics, harvest and storage management, ecosystem services and ethanol yield. A complete field-validated biomass production system has been developed for the Midwest and Central Plains. Even with favorable economic and sustainability results from field trials, switchgrass for bioenergy has not been adopted on a large scale. Lack of adoption is likely due to lower than needed efficiencies for conversion technologies, farmers not wanting to plant switchgrass without a viable bioenergy market and biorefineries not wanting to build without a viable long-term feedstock supply already in place. Answers to 22 of the most pressing questions concerning the feasibility of growing and supplying switchgrass to the biorefinery are provided based on research completed to date. Production, economic, net energy and sustainability research completed to date fully supports the use of switchgrass as a biomass energy crop.